Mitochondrial DNA Leakage Caused by Streptococcus pneumoniae Hydrogen Peroxide Promotes Type I IFN Expression in Lung Cells - Gao, Yue; Xu, Wenchun; Dou, Xiaoyun; Wang, Hong; Zhang, Xuemei; Yang, Shenghui; Liao, Hongyi; Hu, Xuexue; Wang, Hong (Frontiers in Microbiology, 2019)
Streptococcus pneumoniae (S. pn), the bacterial pathogen responsible for invasive pneumococcal diseases, is capable of producing substantial amounts of hydrogen peroxide. However, the impact of S. pn-secreted hydrogen peroxide (H2O2) on the host immune processes is not completely understood. Here, we demonstrated that S. pn-secreted H2O2 caused mitochondrial damage and severe histopathological damage in mouse lung tissue. Additionally, S. pn-secreted H2O2 caused not only oxidative damage to mitochondrial deoxyribonucleic acid (mtDNA), but also a reduction in the mtDNA content in alveolar epithelia cells. This resulted in the release of mtDNA into the cytoplasm, which subsequently induced type I interferons (IFN-I) expression. We also determined that stimulator of interferon genes (STING) signaling was probably involved in S. pn H2O2-inducing IFN-I expression in response to mtDNA damaged by S. pn-secreted H2O2. In conclusion, our study demonstrated that H2O2 produced by S. pn resulted in mtDNA leakage from damaged mitochondria and IFN-I production in alveolar epithelia cells, and STING may be required in this process, and this is a novel mitochondrial damage mechanism by which S. pn potentiates the IFN-I cascade in S. pn infection.